Femoral Stems With Porous Lattice Structures: A Review - Liu, Bolun; Wang, Huizhi; Zhang, Ningze; Zhang, Min; Cheng, Cheng-Kung (Frontiers in Bioengineering and Biotechnology, 2021)
Cementless femoral stems are prone to stress shielding of the femoral bone, which is caused by a mismatch in stiffness between the femoral stem and femur. This can cause bone resorption and resultant loosening of the implant. It is possible to reduce the stress shielding by using a femoral stem with porous structures and lower stiffness. A porous structure also provides a secondary function of allowing bone ingrowth, thus improving the long-term stability of the prosthesis. Furthermore, due to the advent of additive manufacturing (AM) technology, it is possible to fabricate femoral stems with internal porous lattices. Several review articles have discussed porous structures, mainly focusing on the geometric design, mechanical properties and influence on bone ingrowth. However, the safety and effectiveness of porous femoral stems depend not only on the characteristic of porous structure but also on the macro design of the femoral stem; for example, the distribution of the porous structure, the stem geometric shape, the material, and the manufacturing process. This review focuses on porous femoral stems, including the porous structure, macro geometric design of the stem, performance evaluation, research methods used for designing and evaluating the femoral stems, materials and manufacturing techniques. In addition, this review will evaluate whether porous femoral stems can reduce stress shielding and increase bone ingrowth, in addition to analyzing their shortcomings and related risks and providing ideas for potential design improvements.